Variasi Spasi Baut terhadap Kuat Geser Sambungan Baut pada Pelat Baja - Ahmad Sumantri (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2020)
Errors in planning the spaces/distances between the bolts can weaken or create defects in the connection. Therefore, a research on the effect of bolt space on shear strength of bolt joints on steel plates is needed to find out the influence of the distance between bolts to the strength of double bolt joints on steel plate joints, whereas the long-term goal of this study is to determine the effect of the distance between bolts to the strength of the bolt connection in a plate connection system having more than two bolts. In the planning, the connection used bolt connecting devices that meet SNI 1729:2015 requirements. A tensile testing machine was used and the direct test method was conducted for shear strength of bolts in the plate joint system using two bolts. The bolt sample was installed in the plate connection system then the connection system was given a tensile load until it broke in the bolt sample. The peak load of the experimental results indicated the shear strength of the double bolt connection on the plate fluctuates. Average peak load for the sample of group I (20 mm bolt space), group II (40 mm bolt space), group III (60 mm bolt space), group IV (80 mm bolt space) and group V (100 mm bolt space) are 21.962 kN, 23.512 kN, 22.925 kN, 23.725 kN and 22.975 kN, respectively. The experimental results from each sample group showed the average peak load strength was greater than the theoretical shear strength value of 17.4974 kN.